2015
DOI: 10.4253/wjge.v7.i12.1055
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation syndrome: Delayed perforation after colorectal endoscopic treatments

Abstract: Various procedure-related adverse events related to colonoscopic treatment have been reported. Previous studies on the complications of colonoscopic treatment have focused primarily on perforation or bleeding. Coagulation syndrome (CS), which is synonymous with transmural burn syndrome following endoscopic treatment, is another typical adverse event. CS is the result of electrocoagulation injury to the bowel wall that induces a transmural burn and localized peritonitis resulting in serosal inflammation. CS occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 55 publications
1
88
0
1
Order By: Relevance
“…2,33,52,53 The incidence is higher (7%-8%) in patients undergoing ESD. 54 PPES usually is managed with intravenous hydration, broad-spectrum parenteral antibiotics, bowel rest, and nothing by mouth until symptoms subside. 2,53 In a large multicenter study, hypertension, large lesion size (>2 cm), and nonpolypoid morphology were found to be independent predictors of PPES.…”
Section: Postpolypectomy Electrocoagulation Syndromementioning
confidence: 99%
“…2,33,52,53 The incidence is higher (7%-8%) in patients undergoing ESD. 54 PPES usually is managed with intravenous hydration, broad-spectrum parenteral antibiotics, bowel rest, and nothing by mouth until symptoms subside. 2,53 In a large multicenter study, hypertension, large lesion size (>2 cm), and nonpolypoid morphology were found to be independent predictors of PPES.…”
Section: Postpolypectomy Electrocoagulation Syndromementioning
confidence: 99%
“…This full-thickness burn can lead to serosal inflammation and localized peritonitis. 21 Hirasawa et al defined postpolypectomy syndrome (PPS) as a subset of coagulation syndrome resulting after polypectomy or EMR. 21 Patients with PPS usually present with abdominal pain, fever, leukocytosis, elevated C reactive protein (CRP), or signs of localized peritonitis after use of electrocoagulation during colonoscopy.…”
Section: Diagnosismentioning
confidence: 99%
“…Imaging studies do not show any signs of perforation. 21 The incidence of PPS is estimated to be 0.5 to 1.2%. Large lesion size and sessile lesions are risk factors for PPS.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations